Tubastatin alleviates epidural fibrosis via negatively targeting TGFβ/PI3K/Akt pathway: Tubastatin alleviates epidural fibrosis - Tao, Lijiang; Wu, Liangbang; Ge, Yunlin (Cellular and Molecular Biology, 2024)
Epidural fibrosis (EF) is a chronic, progressive and severe disease. Histone deacetylase 6 (HDAC6) regulates biological signals and cell activities by deacetylating lysine residues and participates in TGF-β-induced epithelial-mesenchymal transition (EMT). Nevertheless, the effect and mechanism of HDAC6 in EF remain unclear. To investigate the effect and mechanism of HDAC6 inhibition on repressing epidural fibrosis. HDAC6 expression and α-smooth muscle actin (α-SMA) in normal human tissue and human EF tissue were assessed by quantitative real-time PCR (qRT-PCR) and western blotting. Human fibroblasts were treated with TGF-β ± HDAC6 inhibitors (Tubastatin) and fibrotic markers including collagen I, collagen III, α-SMA and fibronectin were assessed using western blotting. Then TGFβ1 receptor (TGFβ1-R), PI3K and Akt were analyzed using qRT-PCR and western blotting. Rats were undergone laminectomy± Tubastatin (intraperitoneally injection; daily for 7 days) and epidural scar extracellular matrix (ECM) expression was gauged using immunoblots. Increasing HDAC6 expression was associated with α-SMA enrichment. Tubastatin remarkably restrained TGF-β-induced level of collagen and ECM deposition in human fibroblasts, and the discovery was accompanied by decreased PI3K and Akt phosphorylation. Moreover, Tubastatin also inhibited TGF-β-mediated HIF-1α and VEGF expression. In the epidural fibrosis model, we found that Tubastatin weakened scar hyperplasia and collagen deposition, and effectively inhibited the process of epidural fibrosis. These results indicated that Tubastatin inhibited HDAC6 expression and decreased TGF-β/ PI3K/ Akt pathway that promotes collagen and ECM deposition and VEGF release, leading reduction of myofibroblast activation. Hence, Tubastatin ameliorated epidural fibrosis development.